An evaluation of residents perception of identity in Putrajaya new town - Ismail, Ida Suriana; Shamsuddin, Shuhana; Sulaiman, Ahmad Bashri (Faculty of Built Environment, UTM, 2008)
The National Physical Plan highlighted the problem of towns and cities in Malaysia lacking in character and identity. This research foresees that new towns should be able to portray its distinct identity through the design of its physical elements. However, the "created" identity in a new town in certain aspects may differ from that perceived by its inhabitants. Thus, the main interest of the research is to examine the elements and qualities of identity that residents associate with the new town, as compared to what has been created. The research was approached using a mixed method approach with questionnaire, interviews, field observation and content analysis to be its main research tools. This paper presents the research methodology and the initial findings of the questionnaire survey. This paper highlights the aspects that need to be considered in helping to prepare the final stage of in-depth interview, mind-mapping and photo recognition task. The paper concludes by discussing the future direction of the research.